2010
DOI: 10.1111/j.1365-2982.2010.01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mechanisms involved in the intestinal pro-secretory actions of hydrogen sulfide

Abstract: Background H 2 S actions in the gut involve neural activation. This study aimed to reveal the signaling mechanisms responsible for the pro-secretory effect of H 2 S by using TRPV1 and unselective TRP blockers and inhibitors of other signaling cascades hitherto described to be targeted by H 2 S elsewhere. Methods Ussing chamber voltage clamp technique was used to study actions of the H 2 S donor NaHS on secretion in guinea-pig and human colon. NaHS effects on guinea-pig primary afferents were also evaluated. Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 45 publications
3
41
1
Order By: Relevance
“…Furthermore, previous studies have also linked H 2 S to TRPA1 and microvascular blood flow mediated by CGRP53 and H 2 S and TRPA1/TRPV1 intestinal pro-secretory actions54. However, only very high concentrations of H 2 S activated TRPA1 (as we also observed, Supplementary Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, previous studies have also linked H 2 S to TRPA1 and microvascular blood flow mediated by CGRP53 and H 2 S and TRPA1/TRPV1 intestinal pro-secretory actions54. However, only very high concentrations of H 2 S activated TRPA1 (as we also observed, Supplementary Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Of note is that recent studies showed that sodium channels are not the sole target of H 2 S-induced pain hypersensitivity. T-type calcium channels2324, TRPV12526, TRPA120 and NMDA receptors27 have been indicated to play a crucial role in nociception. Conversely, H 2 S has been reported to mediate an anti-nociceptive effect by opening K(ATP) channels2829 and to prevent the development of opioid withdrawal-induced hyperalgesia by suppressing spinal calcitonin gene-related peptide expression30.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, H 2 S enhances NMDA receptormediated responses during tetanic nerve stimulation in the hippocampus (Abe and Kimura, 1996;Tan et al, 2010;Austgen et al, 2011), reversibly inhibits synaptic responses in dorsal raphe serotonergic neurons (Kombian et al, 1993), and augments synaptic neurotransmission in the rat nucleus tractus solitarius (Austgen et al, 2011). In the peripheral nervous system, H 2 S induces contraction of the bladder wall (Patacchini et al, 2004) and acts on enteric neurons in the human and guinea pig colon to increase chloride secretion (Schicho et al, 2006;Krueger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%